2005
DOI: 10.1108/00400910510580629
|View full text |Cite
|
Sign up to set email alerts
|

The nature and purpose of the DBA

Abstract: Purpose -To explore the nature (component parts, degree structure) and purpose (intended outcomes) of the Doctor of Business Administration (DBA) degree, identifying the strengths and weaknesses of the degree as they stand presently, using Australian experience. Design/methodology/approach -A review of DBA programme offerings in Australia identified commonalities and differences in these offerings, and provided information necessary to propose strategic and theoretical implications of DBA education. Findings -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 10 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Second, the purpose and value of the professional doctorate is presented in terms of professional development and not as research-based learning. Researchers across the globe have criticised professional doctorates as a poor alternative to the PhD; lacking in intellectual rigour and research-orientated skills in the UK and Canada (Winter et al, 2000;Allen et al, 2002) or a lack of quality controls over their growth in Australia (Sarros et al, 2005). For McWilliam et al (2002McWilliam et al ( , p. 1104 although the DBA and PhD are "differently rigorous […], there is little consistency in how these graduate degree programmes are delivered, monitored, and evaluated".…”
Section: Introductionmentioning
confidence: 99%
“…Second, the purpose and value of the professional doctorate is presented in terms of professional development and not as research-based learning. Researchers across the globe have criticised professional doctorates as a poor alternative to the PhD; lacking in intellectual rigour and research-orientated skills in the UK and Canada (Winter et al, 2000;Allen et al, 2002) or a lack of quality controls over their growth in Australia (Sarros et al, 2005). For McWilliam et al (2002McWilliam et al ( , p. 1104 although the DBA and PhD are "differently rigorous […], there is little consistency in how these graduate degree programmes are delivered, monitored, and evaluated".…”
Section: Introductionmentioning
confidence: 99%
“…While there has been some confusion about the relative emphases of professional doctorates compared to the research PhD (Sarros et al 2005), they nevertheless ground students thoroughly in research methodology via coursework. We believe that the education of Australian postgraduates in the natural resource fields should emulate this approach, but it will take time and resources to achieve this.…”
Section: Contrasting Models Of University Education: Australia and Thmentioning
confidence: 99%
“…Furthermore, recent research has identified the value of 'collective academic supervision', with multiple supervisors working with students to create the best environment for students to learn core academic competencies (Nordentoft et al 2013). This can also balance the 'tough love' approach of some supervisors, who deliberately create a critical environment for their students who need to rise to the expectations or leave (Aitchison et al 2012).Many overseas universities and some disciplines in Australian universities have responded to these evolving requirements for providing fundamental skills to research students with postgraduate courses within higher degrees by research to cover critical learning skills, provide peer-learning interactions amongst students and expose students to a wide range of subject experts (e.g., Maxwell and Shanahan 1997;Sarros et al 2005;Stephenson et al 2006; Rolfe and Davies 2009; Chiteng Kot and Henda 2012). These are known variously as researchcoursework doctoral programs (Trigwell et al 1997), professional doctorates (Chiteng Kot and Henda 2012), professional research doctorates (Nerad 2007), or workbased doctorates if they involve significant practitioner liaison (Costley and Lester 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation